Health-related quality of life and recovery capital among recovery residents taking medication for opioid use disorder in Texas - Obekpa, Elizabeth O.; McCurdy, Sheryl A.; Schick, Vanessa; Markham, Christine M.; Gallardo, Kathryn R.; Wilkerson, Johnny Michael (Frontiers in Public Health, 2023)
Background Recovery from opioid use disorder (OUD) includes improvements in health-related quality of life (HRQOL) and is supported by recovery capital (RC). Little is known about RC and HRQOL among recovery residents taking medication for OUD. We described HRQOL and RC and identified predictors of HRQOL. Methods Project HOMES is an ongoing longitudinal study implemented in 14 recovery homes in Texas. This is a cross-sectional analysis of data from 358 participants’ on HRQOL (five EQ-5D-5L dimensions—mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) and RC (Assessment of Recovery Capital scores) collected from April 2021 to June 2023. Statistical analyses were conducted using T-, Chi-squared, and Fisher’s exact tests. Results Most participants were 35 years/older (50.7%), male (58.9%), non-Hispanic White (68.4%), heterosexual (82.8%), and reported HRQOL problems, mainly anxiety/depression (78.4%) and pain/discomfort (55.7%). Participants who were 35 years/older [mean (SD) = 42.6 (7.3)] were more likely to report mobility and pain/discomfort problems than younger participants. Female participants were more likely to report pain/discomfort problems than male participants. Sexual minorities were more likely to report anxiety/depression problems than heterosexual participants. Married participants and those in committed relationships were more likely to report problems conducting self-care than single/never-married participants. Comorbid conditions were associated with mobility, pain/discomfort, and usual activities problems. Most participants reported high social (65.4%), personal (69.0%), and total (65.6%) RC. Low personal RC was associated with mobility (aOR = 0.43, CI = 0.24–0.76), self-care (aOR = 0.13, CI = 0.04–0.41), usual activities (aOR = 0.25, CI = 0.11–0.57), pain/discomfort (aOR = 0.37, CI = 0.20–0.68), and anxiety/depression (aOR = 0.33, CI = 0.15–0.73) problems. Low total RC was associated with problems conducting self-care (aOR = 0.20, CI = 0.07–0.60), usual activities (aOR = 0.43, CI = 0.22–0.83), pain/discomfort problems (aOR = 0.55, CI = 0.34–0.90), and anxiety/depression (aOR = 0.20, CI = 0.10–0.41) problems. Social RC was not associated with HRQOL. Conclusion Personal and total RC and comorbid conditions predict HRQOL. Although the opioid crisis and the increasing prevalence of comorbidities have been described as epidemics, they are currently being addressed as separate public health issues. Our findings underscore the importance of ensuring residents are provided with interprofessional care to reduce the burden of comorbidities, which can negatively impact their OUD recovery. Their RC should be routinely assessed and enhanced to support their recovery and improve HRQOL.